Fundamentalism, Revivalists, and Violence in South Asia: Edited by James Warner Bjorkman Riverdale Company, Riverdale, MD 1988, 193 pp. (American Journal of Islam and Society, 1989)
The volume under review is essentially a collection of papers presentedat a two-day workshop on the changing division of labor in South Asia heldat the University of Wisconsin in 1984 at which the two major themes werethe emerging role of women; and the “increasingly violent role of religion.”IThe latter theme became the subject of this book.Concerning this subject, the editor, Dr. Bjorkman, writes:“If, then, you have been perplexed about the chronic religiousviolence in contemporary South Asian states, you need search nofurther for relief. The following chapters examine, explore, andexplain aspects of religious fundamentalism, self-righteousrevivalists, and murderous mayhem among the four major faithsof South Asia."Then, evincing his concern for the human situation in the area, and hisown obviously painful experiences there, Dr. Bjorkman continues:“. . . one may justifiably conclude that a no-win situationcharacterizes the South Asian mosaic. Contemporary reality isdepressing, if not gruesome; the daily documentation of death anddestruction, cruelty and carnage, is sufficient evidence thereof?Candidly assessing the objective of his work, Dr. Bjorkman states:“The aim of this book is to uncover some of the socio-politicaltruths disguised by the frequent invocation of “fundamentalist” and“revivalist” claims in contemporary South Asian religions.”And in order to prepare the reader for what lies ahead, the learned editoradds:“One can come away from this volume wringing one’s hands indespair at the utter hopelessness of human foibles. Or one cancatch glimpses of truth and possible points of leverage by whichthe certain slide into anarchy might be arrested and even reversed.Sigmund Freud once wrote: ‘The truths contained in religious doctrinesare after all so distorted and systematically disguised thatthe mass of mankind cannot recognize them as truth (Freud1928 :78) .“Thus, before moving on to even the editor’s introductory chapter, theinterested reader, in the sense of his or her faith or allegiance to one or theother of the four major religions of South Asia, will begin to feel queasyat the prospect of what lies ahead. Many such, I suspect, will put the volumedown and start wringing their own hands at the utter hopelessness of humanfoibles in the guise of Western academic treatments of Eastern affairs of thespirit. But no, gentle reader, dismay not; the volume is not your averagewitch hunt. On the contrary, as food for thought it is immediately engaging,and as an opportunity for self-exam ...